2010
DOI: 10.3201/eid1604.090695
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia albertiiin Wild and Domestic Birds

Abstract: The isolates were similar to those that cause disease in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
132
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(139 citation statements)
references
References 30 publications
7
132
0
Order By: Relevance
“…This pathogen was isolated from feces of wild or domestic birds which include chickens (7). These findings suggest that raw chicken is a potential source of E. albertii food poisoning.…”
Section: Communicated By Makoto Ohnishimentioning
confidence: 86%
See 1 more Smart Citation
“…This pathogen was isolated from feces of wild or domestic birds which include chickens (7). These findings suggest that raw chicken is a potential source of E. albertii food poisoning.…”
Section: Communicated By Makoto Ohnishimentioning
confidence: 86%
“…A multiplex PCR was performed to amplify the lysP and mdh genes, to detect unique polymorphisms of E. albertii (9), and the clpX gene, which is conserved in E. coli, Shigella, and the E. albertii/S. boydii lineage (7,9). The PCR test revealed that FCI-ALB001 strain harbored lysP, mdh, and clpX (Fig.…”
Section: Communicated By Makoto Ohnishimentioning
confidence: 99%
“…E. albertii is very similar to E. coli in terms of its biochemical properties, and it possesses a large chromosomal pathogenicity island, termed the locus of enterocyte effacement, which is involved in the formation of attaching and effacing lesions, similar to EPEC. Thus, several E. albertii strains have been misidentified as EPEC (18,21). In contrast to EPEC, a proportion of E. albertii strains harbor various toxin genes, including cdt (orthologs of E. coli cdt-I and cdt-II) and/ or stx2 (stx2a and stx2f) (18,22).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to EPEC, a proportion of E. albertii strains harbor various toxin genes, including cdt (orthologs of E. coli cdt-I and cdt-II) and/ or stx2 (stx2a and stx2f) (18,22). Since there are only a limited number of reports on the isolation and identification of E. albertii (18)(19)(20)(21)(22)(23)(24), more epidemiological information is needed to understand its pathogenicity and properties. In the present study, we identified a bacterium harboring cdt-I, cdt-II, and stx2f as E. albertii, which was isolated from a pediatric patient with diarrhea in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…using routine bacterial identification systems based on biochemical properties (5)(6)(7)(8). Actually E. albertii represents a substantial proportion of the strains that had previously been identified as EPEC and EHEC in the case of stx-positive strains (9).…”
mentioning
confidence: 99%